2021
DOI: 10.3389/fcvm.2021.721850
|View full text |Cite
|
Sign up to set email alerts
|

Sex Differences in Characteristics and Outcomes in Elderly Heart Failure Patients With Preserved Ejection Fraction: A Post-hoc Analysis From TOPCAT

Abstract: Introduction: Although the impact of sex on patient outcomes for heart failure (HF) with preserved ejection fraction (HFpEF) has been reported, it is still unclear whether this impact is applicable for elderly patients with HFpEF. This study was conducted as a secondary analysis from a large randomized controlled trial—The Treatment of Preserved Cardiac Function Heart Failure with an Aldosterone Antagonist Trial (TOPCAT)—to evaluate the impact of sex differences on the baseline characteristics and outcomes of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…HFpEF can also be the manifestation of specific cardiomyopathies, such as inherited or acquired infiltrative cardiomyopathies (including cardiac amyloidosis), restrictive cardiomyopathies, myocarditis, or genetic cardiomyopathies [ 120 ]. Notably, women with HFpEF have a better prognosis than men with HFpEF, with less mortality despite a higher re-hospitalization rate, which could possibly reflect a sex difference in spironolactone treatment impact on all-cause mortality [ 122 ].…”
Section: Sex Differences In Cardiovascular Diseases and Their Impact ...mentioning
confidence: 99%
“…HFpEF can also be the manifestation of specific cardiomyopathies, such as inherited or acquired infiltrative cardiomyopathies (including cardiac amyloidosis), restrictive cardiomyopathies, myocarditis, or genetic cardiomyopathies [ 120 ]. Notably, women with HFpEF have a better prognosis than men with HFpEF, with less mortality despite a higher re-hospitalization rate, which could possibly reflect a sex difference in spironolactone treatment impact on all-cause mortality [ 122 ].…”
Section: Sex Differences In Cardiovascular Diseases and Their Impact ...mentioning
confidence: 99%
“…Data on mortality and hospitalization, however, are not consistent. Three studies reported significantly better outcomes in women with HFpEF compared to men with HFpEF [ 55 , 131 , 132 ]. Also, women with HF were more frequently admitted for non-cardiovascular causes [ 130 ], and women hospitalized with HFpEF were at higher risk of poor post-discharge outcomes (adjusted HR = 1.54 (95% CI: 1.14, 2.07) than men [ 133 ], which may be due to high comorbidity burden in women.…”
Section: Mainmentioning
confidence: 99%
“…Also, women with HF were more frequently admitted for non-cardiovascular causes [ 130 ], and women hospitalized with HFpEF were at higher risk of poor post-discharge outcomes (adjusted HR = 1.54 (95% CI: 1.14, 2.07) than men [ 133 ], which may be due to high comorbidity burden in women. This high comorbidity burden together with a higher prevalence of obesity and worse diastolic and vascular function and greater exercise limitations might reflect different HFpEF etiologies and can partly explain the inconsistencies in prognostic studies [ 39 , 131 , 134 , 135 ]. Additionally, women with HFpEF have a worse quality of life compared to men with HFpEF, and this is also consistently observed in the general community [ 134 ].…”
Section: Mainmentioning
confidence: 99%
“… 9 Although women and men share the same risk for adverse outcomes in heart failure with reduced ejection fraction, inconsistent evidence exists on differing mortality rates in between both sexes in HFpEF. 10 , 11 , 12 Varying onset of symptomatic burden initiating clinical consultation and differences in disease progression within both sexes could be a reason to heterogeneous mortality rates. 13 Female patients tend to be more prone to metabolic stress than men 14 and have an increased risk of congestive heart failure as a response to hypertension.…”
mentioning
confidence: 99%